Intensi tidur cukup mahasiswa berdasarkan Theory Of Planned Behavior: Analisis Structural Equation Modelling - Valentino, Kenny; Sunardy, Grace Natasha; Andriani, Dhini; Hinduan, Zahrotur Rusyda (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2022)
Abstract Adequate sleep is essential since short sleep duration can cause various adverse effects. Previous research found that college students often find it difficult and have low intentions to get enough sleep due to several factors. This study aims to see the role of adequate sleep intention factors based on the Theory of Planned Behavior in college students, namely attitude toward behavior, subjective norm, and perceived behavioral control. Participants were 600 college students at a state university in Indonesia. The data was obtained through a questionnaire adapted from the Theory of Planned Behavior Questionnaire (α=0,793) and statistically analyzed using Structural Equation Modeling and Kruskal-Wallis. The results show that attitude toward behavior, subjective norm, and perceived behavioral control had a significant role in predicting adequate sleep intention in college students. Furthermore, attitude toward behavior has the most substantial role among the other factors. Through this research, future interventions that aim college students’ sleep intention can focus on targeting students’ attitude toward sleep behavior. Keywords: adequate sleep; college students; sleep intention; structural equation modelling; theory of planned behavior Abstrak Tidur cukup sangat penting bagi manusia dan kurangnya waktu tidur dapat menyebabkan berbagai dampak negatif. Pada penelitian sebelumnya, ditemukan bahwa mahasiswa sering mengalami kesulitan dan memiliki intensi yang rendah untuk tidur cukup karena berbagai faktor. Penelitian ini bertujuan untuk melihat peran faktor-faktor yang mendasari intensi tidur cukup berdasarkan Theory of Planned Behavior pada mahasiswa, yaitu attitude toward behavior, subjective norm, dan perceived behavioral control. Partisipan pada penelitian ini adalah 600 mahasiswa salah satu perguruan tinggi negeri di Indonesia. Data diperoleh dengan menggunakan kuesioner yang diadaptasi dari Theory of Planned Behavior Questionnaire (α=0,793) dan dianalisis secara statistik dengan Structural Equation Modeling serta Kruskal-Wallis. Hasil menunjukkan bahwa attitude toward behavior, subjective norm, dan perceived behavioral control berperan secara signifikan terhadap intensi tidur cukup mahasiswa. Adapun faktor yang memiliki peran terbesar dalam memprediksi intensi tidur cukup pada mahasiswa adalah attitude toward behavior. Melalui hasil penelitian ini, para praktisi dapat menyasar sikap mahasiswa terhadap perilaku tidur cukup saat hendak merancang intervensi tidur cukup pada mahasiswa. Kata kunci: intensi; mahasiswa; structural equation modelling; theory of planned behavior; tidur cukup